Możliwości wykorzystania metafor konwencjonalnych w nauczaniu słownictwa i frazeologii języków obcych na przykładzie języka polskiego jako obcego - Kuc, Maria; Rabczuk, Anna (Neofilolog, 2024)
The article discusses the use of conventional metaphors, proposed by G. Lakoff and M. Johnson, as a tool for teaching vocabulary and phraseology at advanced levels of language proficiency in the context of learning Polish as a foreign language. As this methodology is insufficiently represented in teaching materials, the article highlights the advantages of a systematic and long-term approach to teaching metaphors. Such advantages include deepening knowledge of vocabulary by a consideration of metaphorical meanings, understanding the role of metaphors in mental processes; providing insights into Polish culture and mentality as well as into the students’ own cultures, as expressed through their native languages; and stimulating students’ mediation skills. The article also provides examples of exercises to aid the discovery of different types of conventional metaphors and establish an understanding of their function. It concludes by emphasizing the importance of developing collections of exercises and projects – in both printed and interactive forms — to support language learners. Overall, the article promotes the use of conventional metaphors as an effective method for improving linguistic and communicative competence in foreign language learning.